A Case Study of Complex Care Management at a Student-Run Free Clinic - Nourse, Susan E; Franco, Christine L; Johnson, Emily H; Williams, Brent C (Journal of Student-Run Clinics, 2019)
Free clinics are an essential part of the United States health care safety net, and student-run free clinics comprise a significant proportion of free clinics nationally. These clinics operate with limited resources but see a population of medically and socially complex patients. Complex care management is a spectrum of care models targeting high-need, high-cost patients designed to improve outcomes and reduce overutilization of health care which have been implemented in many health care settings. Common features of care management programs include patient selection, specialized care managers, and multidisciplinary medical teams. Patients seen at student-run free clinics would benefit from the principles of complex care management. The principles of complex care management have been incorporated into patient care at the University of Michigan Student-Run Free Clinic (UMSRFC) as part of a pilot care management protocol. Patients seen from May 2016 through April 2017 during the first year of the program’s implementation were included in this descriptive report. Approximately 30 patients out of 208 unique patients seen from May 2016-April 2017 were considered complex and managed according to this protocol. Three representative patients were selected as illustrative examples by the authors and their care is described. Features that complicated the care of these patients included uninsured status, insurance ineligibility, poor health literacy, inability to afford medications, multiple comorbid chronic health conditions, mental health disorders, and difficulty with telephone communication. Their outcomes included one patient being successfully transitioned to established health care systems, one patient establishing continuity of care at the UMSRFC with improved management of chronic health conditions, and one patient being lost to follow up. Principles of complex care management may be able to be adapted to fit the limitations of the student-run free clinic model. The implementation of these programs may improve health care outcomes for patients with complex needs.